Meningkatkan Literasi Numerisasi Siswa Literasi Media Pembelajaran Nilai Tempat Dan Bangun Datar SD Pelangi Jimbaran - Ginantra, Ni Luh Wiwik Sri Rahayu; Dewi, Ni Wayan Jeri Kusuma; Indra Pratistha (LPPM POLITEKNIK LP3I, 2025)
Numeracy literacy skills are a fundamental foundation in mathematics learning at the elementary school level, particularly in topics such as place value and plane geometry. However, initial observations at SD Pelangi Jimbaran indicate that fifth-grade students still experience difficulties in understanding numerical concepts both conceptually and contextually. Learning tends to be procedural and oriented toward rote memorization, with limited support from interactive, technology-based learning media. This community service activity aims to enhance students’ understanding and learning interest through the development of interactive learning media based on Canva. The implementation methods include observation and needs analysis, media design, production and pilot testing, as well as evaluation and dissemination. The media were developed in the form of educational visual presentations and digital activity worksheets that present concrete and contextual visualizations of place value and plane geometry. The results of the implementation show increased student engagement, improved conceptual understanding, and positive responses from partner teachers. The program also enhances teachers’ capacity in utilizing digital media and strengthens collaboration between higher education institutions and elementary schools. Thus, Canva-based learning media have proven to be an effective innovative solution for strengthening numeracy literacy in elementary schools